Distribusi Belanja Desa dan Capaian Status Pembangunan Desa di Provinsi Riau - Bakti Kharisma; Werry Darta Taifur; Fajri Muharja (Ekonomis: Journal of Economics and Business, 2021)
The Village Law has become one of the berakhthroughs in overcoming the impact of development that tends to be urban bias. Village is no longer only an object of development but the main actor in rural development process. The source of the budget for the implamentation of rural development has increased significantly with the village fund policy. This study aims to analyze the impact of village budgets and village typology on the achievement of village status in Riau Province. Multiple linear regression model was used to analyze the impact of village budget and village typology has a significant impact on the increase in the developing village index in Riau Province.